A three-phase composite sodium storage material and its preparation method and application
By using three-phase composite sodium storage material (FeS)x/(V3S4)y/C in sodium ion batteries, the synergistic effect of the heterogeneous interface of FeS and V3S4 and the carbon material is solved. The electrochemical performance of sodium ion batteries is reduced. Problem, improving cycle stability and rate performance, extending the battery life.
Patent Information
- Application Number
- CN202410991820.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-23
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-07-23
AI Technical Summary
The electrochemical performance of sodium ion batteries decreases rapidly during charging and discharging, affecting the cycle stability and rate performance.
Using three-phase composite sodium storage material (FeS)x/(V3S4)y/C, a heterogeneous interface is formed through FeS and V3S4, increasing the sodium ion storage site and conductivity, and the carbon material forms a tight interface with FeS and V3S4 to enhance electricity. Chemical properties and inhibit structural damage of electrode materials.
It improves the cycle stability and rate performance of sodium ion batteries, extends the service life of the battery, and reduces the specific capacity reduction and electrochemical impedance of the electrode material.
Smart Images

Figure CN118676347B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a three-phase composite sodium storage material and a preparation method and application thereof. Background Art
[0002] Sodium-ion batteries have the advantages of low cost, high safety and fast charging capability, and have broad application prospects in the field of energy storage. During the charging and discharging process of sodium-ion batteries, sodium ions will migrate to the positive and negative electrodes and be stored in the corresponding positive and negative electrode materials. The amount and speed of sodium ions in the positive and negative electrodes have an important influence on the cycle stability and rate performance of the electrode materials. The cycle stability and rate performance of the electrode materials affect the electrochemical properties of sodium-ion batteries.
[0003] In some examples, sulfide sodium storage materials can be used as negative electrode materials for sodium ion batteries. For example, the electrochemical performance of sodium ion batteries can be improved by designing the morphology of the sodium sulfide sodium storage materials. However, during the charge and discharge process of sodium ion batteries, there is still a disadvantage that the electrochemical performance of sodium ion batteries decreases rapidly. Summary of the invention
[0004] The purpose of the present application is to provide a three-phase composite sodium storage material and a preparation method and application thereof, in order to solve the problem that the electrochemical performance of sodium ion batteries decreases rapidly during charging and discharging.
[0005] In order to achieve the above objectives, this application adopts the following technical solutions:
[0006] In a first aspect, an embodiment of the present application provides a three-phase composite sodium storage material. The three-phase composite sodium storage material is selected from any one of the structures shown in the following general formula: (FeS) x / (V3S4) y / C; where 0.2≤x≤5, 0.2≤y≤5.
[0007] In the three-phase composite sodium storage material (FeS) provided in the embodiment of the present application x / (V3S4) y / C, firstly, FeS and V3S4 can form a heterogeneous interface, at which the adsorption energy required for sodium storage is low, making it easier for sodium ions to be adsorbed, thus increasing the amount of sodium ion storage in the three-phase composite sodium storage material; moreover, (FeS) x / (V3S4) yThere are a large number of point defects, line defects and surface defects in the bulk phase of / C, which can provide a large number of sodium ion storage sites, which can further increase the number of sodium ion storage in the three-phase composite sodium storage material, so that the three-phase composite sodium storage material has a good specific capacity, thereby making the number of sodium ions released and embedded in the positive and negative electrodes of the sodium ion battery larger. During the charge and discharge process of the sodium ion battery, the specific capacity of the battery electrode material decreases less.
[0008] Secondly, (FeS) x / (V3S4) y The bulk phase of FeS / C contains a large number of defects, which can form a large number of free electrons and holes, which can improve the conductivity of the three-phase composite sodium storage material and accelerate the migration rate of sodium ions; (FeS) x / (V3S4) y The large number of defects contained in the bulk phase of (FeS) / C can also enhance the electrochemical power of the three-phase composite sodium storage material, making the resistance to the migration of sodium ions relatively small; moreover, x / (V3S4) y The large number of defects contained in the bulk phase of / C can also provide more ion channels for the migration of sodium ions, which helps to accelerate the migration of sodium ions, thereby increasing the speed of sodium ion extraction and embedding in the positive and negative electrodes, which can improve the rate performance of sodium ion battery electrode materials and reduce impedance.
[0009] Furthermore, the carbon material in the three-phase composite sodium storage material, on the one hand, can form a close interface with FeS and V3S4, serve as a bridge or medium for the formation of the heterogeneous interface between FeS and V3S4, and promote the formation and stability of the heterogeneous interface; on the second hand, the carbon material has good electrical conductivity, which can improve the electrochemical properties of the three-phase composite sodium storage material; on the third hand, the carbon material has good mechanical strength and ductility, can inhibit the volume expansion of the electrode material, reduce the structural damage of the electrode material, and reduce the shedding of active substances on the electrode material, thereby ensuring the stability of the three-phase composite sodium storage material during the charging and discharging process of the sodium ion battery electrode material, reducing the impedance of the electrode material, and thereby improving the cycle life of the sodium ion battery.
[0010] Therefore, through the synergistic effect between the FeS, V3S4 and C materials, the cycle stability and rate performance of the three-phase composite sodium storage material as an electrode material can be improved, thereby solving the problem of rapid decline in electrochemical performance of sodium-ion batteries during charging and discharging.
[0011] In some embodiments, the average particle size of the three-phase composite sodium storage material is in the range of 4 μm to 10 μm.
[0012] In some embodiments, the three-phase composite sodium storage material has a specific capacity in the range of 500 mAh / g to 600 mAh / g after 150 to 200 cycles at a current density in the range of 0.8 A / g to 1.2 A / g.
[0013] In some embodiments, the specific capacity of the three-phase composite sodium storage material decreases by less than or equal to 25% after 1000 cycles under a current density range of 3.8 A / g to 4.2 A / g.
[0014] In some embodiments, the initial electrochemical impedance of the three-phase composite sodium storage material is in the range of 0.015Ω~0.020Ω.
[0015] In a second aspect, the embodiments of the present application also provide a method for preparing a three-phase composite sodium storage material. The method comprises: reacting an iron source and a vanadium source under alkaline conditions to obtain a first precipitate; hydrothermally reacting a carbon source, the first precipitate and a sulfur source in an organic solvent to obtain a second precipitate; calcining the second precipitate under inert gas conditions to obtain a three-phase composite sodium storage material; the three-phase composite sodium storage material is selected from any one of the structures shown in the following general formula: (FeS) x / (V3S4) y / C, where 0.2≤x≤5; 0.2≤y≤5.
[0016] In some embodiments, the iron source includes at least one of ferric chloride, ferrous chloride, ferric sulfate, ferric oxalate, and ferric nitrate.
[0017] In some embodiments, the vanadium source includes at least one of vanadium chloride, vanadium oxide, and vanadium oxalate.
[0018] In some embodiments, the sulfur source includes at least one of thiourea, thioacetamide, and sulfur powder.
[0019] In some embodiments, the carbon source comprises at least one of polyvinylpyrrolidone, glucose, polypyrrolidone, and polydopamine.
[0020] In some embodiments, the molar ratio of the iron source to the vanadium source ranges from 0.2 to 5.
[0021] In some embodiments, the molar ratio of the iron source to the sulfur source ranges from 2 to 5.
[0022] In some embodiments, the mass of the carbon source is 10% to 20% of the total mass of the iron source, the sulfur source, and the vanadium source.
[0023] In some embodiments, the first precipitate includes at least one of iron oxide, iron hydroxide, vanadium oxide, and vanadium hydroxide.
[0024] In some embodiments, the second precipitate includes at least one of an iron-sulfur compound and a vanadium-sulfur compound.
[0025] In a third aspect, an embodiment of the present application also provides an application of the three-phase composite sodium storage material described in any of the above embodiments in a sodium ion battery electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0027] Figure 1 This is a flow chart of a method for preparing a three-phase composite sodium storage material according to some embodiments of the present application;
[0028] Figure 2 This is an X-ray diffraction pattern of the three-phase composite sodium storage material of Example 1 of the present application;
[0029] Figure 3 This is a scanning electron microscope image of the three-phase composite sodium storage material of Example 1 of the present application;
[0030] Figure 4 This is a scanning electron microscope image of the three-phase composite sodium storage material of Example 1 of the present application;
[0031] Figure 5 This is a transmission electron microscope image of the three-phase composite sodium storage material of Example 1 of the present application;
[0032] Figure 6 This is a scanning electron microscope image of the three-phase composite sodium storage material of Example 2 of the present application;
[0033] Figure 7 This is a scanning electron microscope image of the sodium storage material of Comparative Example 1 of the present application;
[0034] Figure 8 This is a scanning electron microscope image of the sodium storage material of Comparative Example 2 of the present application;
[0035] Fig. 9 A comparison chart of the discharge specific capacities of the sodium storage materials of Example 1, Comparative Example 1 and Comparative Example 2 of the present application;
[0036] Fig.10 This is a comparison chart of the charge specific capacity and discharge specific capacity of the three-phase composite sodium storage material of Example 1 of the present application;
[0037] Fig.11 A comparison chart of the initial electrochemical impedance of the sodium storage materials of Example 1, Comparative Example 1 and Comparative Example 2 of the present application;
[0038] Fig.12 This is a comparison chart of the rate performance of the sodium storage materials of Example 1, Comparative Example 1 and Comparative Example 2 of the present application. DETAILED DESCRIPTION
[0039] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0040] In the present application, the terms "comprises", "comprising" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, article or device. In the absence of further restrictions, an element defined by the sentence "comprising a ..." does not exclude the presence of other identical elements in the process, article or device including the element.
[0041] In the embodiments of the present application, words such as "exemplary" or "for example" are used to indicate examples, illustrations or descriptions. Any embodiment or design described as "exemplary" or "for example" in the embodiments of the present application should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of words such as "exemplary" or "for example" is intended to present related concepts in a specific way.
[0042] In the description of this specification, specific features, structures, materials or characteristics may be combined in an appropriate manner in any one or more embodiments or examples.
[0043] In some embodiments, due to the influence of the structural properties of the sodium ion battery electrode material itself, the electrode material has low conductivity, electrochemical kinetic hysteresis, and a high expansion rate, which causes the sodium ion battery to have a large decrease in specific capacity during the charge and discharge process, and poor cycle capacity and rate performance, ultimately causing the sodium ion battery to have a faster decline in electrochemical performance, affecting the service life and application range of the sodium ion battery.
[0044] Based on this, in the first aspect, the embodiments of the present application provide a three-phase composite sodium storage material. The three-phase composite sodium storage material is selected from any one of the structures shown in the following general formula: (FeS) x / (V3S4) y / C; where 0.2≤x≤5, 0.2≤y≤5.
[0045] In the three-phase composite sodium storage material (FeS) provided in the embodiment of the present application x / (V3S4) y / C, firstly, FeS and V3S4 can form a heterogeneous interface, at which the adsorption energy required for sodium storage is low, making it easier for sodium ions to be adsorbed, thus increasing the amount of sodium ion storage in the three-phase composite sodium storage material; moreover, (FeS) x / (V3S4) y There are a large number of point defects, line defects and surface defects in the bulk phase of / C, which can provide a large number of sodium ion storage sites, which can further increase the number of sodium ion storage in the three-phase composite sodium storage material, so that the three-phase composite sodium storage material has a good specific capacity, thereby making the number of sodium ions released and embedded in the positive and negative electrodes of the sodium ion battery larger. During the charge and discharge process of the sodium ion battery, the specific capacity of the electrode material decreases less.
[0046] Secondly, (FeS) x / (V3S4) y The bulk phase of FeS / C contains a large number of defects, which can form a large number of free electrons and holes, which can improve the conductivity of the three-phase composite sodium storage material and accelerate the migration rate of sodium ions; (FeS) x / (V3S4) y The large number of defects contained in the bulk phase of (FeS) / C can also enhance the electrochemical power of the three-phase composite sodium storage material, making the resistance to the migration of sodium ions relatively small; moreover, x / (V3S4) y The large number of defects contained in the bulk phase of / C can also provide more ion channels for the migration of sodium ions, which helps to accelerate the migration of sodium ions, thereby increasing the speed of sodium ion extraction and embedding in the positive and negative electrodes, which can improve the rate performance of the electrode material of the sodium ion battery and reduce the impedance.
[0047] Furthermore, the carbon material in the three-phase composite sodium storage material, on the one hand, can form a close interface bonding with FeS and V3S4, and serve as a bridge or medium for the formation of the heterogeneous interface between FeS and V3S4, thereby promoting the formation and stability of the heterogeneous interface; on the second hand, the carbon material has good electrical conductivity, which can improve the electrochemical properties of the three-phase composite sodium storage material; on the third hand, the carbon material has good mechanical strength and ductility, which can inhibit the volume expansion of the electrode material, reduce the structural damage of the electrode material, and reduce the shedding of active substances on the electrode material, thereby ensuring the stability of the three-phase composite sodium storage material during the charging and discharging process of the sodium ion battery, reducing the impedance of the electrode material, and thereby improving the cycle life of the sodium ion battery.
[0048] Therefore, the synergistic effect between the FeS, V3S4 and C materials can greatly improve the cycle stability and rate performance of the three-phase composite sodium storage material, thereby solving the problem of rapid decline in electrochemical performance of sodium-ion batteries during charging and discharging.
[0049] In some embodiments, the average particle size of the three-phase composite sodium storage material is in the range of 4 μm to 10 μm.
[0050] Exemplarily, the average particle size of the three-phase composite sodium storage material can be 4 μm, 6 μm, 8 μm or 10 μm, etc., which is not limited here.
[0051] When the average particle size of the three-phase composite sodium storage material is too large, for example, greater than 10 μm, the stability of the material structure may be reduced during the charge and discharge process of the sodium ion battery; when the average particle size of the three-phase composite sodium storage material is too small, for example, less than 4 μm, the three-phase composite sodium storage material may be agglomerated, affecting the performance of the three-phase composite sodium storage material, resulting in a decrease in battery capacity and battery cycle performance. By setting the average particle size range of the three-phase composite sodium storage material to 4 μm~10 μm, the stability of the three-phase composite sodium storage material structure can be improved, which is beneficial to the diffusion of sodium ions, thereby improving the electrochemical performance of the sodium ion battery.
[0052] In some embodiments, the three-phase composite sodium storage material has a specific capacity of 500 mAh / g to 600 mAh / g after 150 to 200 cycles at a current density of 0.8 A / g to 1.2 A / g. Specific capacity refers to the amount of electricity that can be released by a battery or active material per unit weight, and is an important indicator of battery performance.
[0053] Exemplarily, the three-phase composite sodium storage material can have a specific capacity of 500mAh / g, 520mAh / g, 550mAh / g, 560mAh / g, 580mAh / g or 600mAh / g, etc. after 150 to 200 cycles at a current density of 1A / g, but there is no limitation here.
[0054] Therefore, the three-phase composite sodium storage material provided in the embodiments of the present application has a higher specific capacity.
[0055] In some embodiments, the specific capacity of the three-phase composite sodium storage material decreases by less than or equal to 25% after 1000 cycles at a current density in the range of 3.8A / g to 4.2A / g. Cycling performance refers to charging and discharging the battery at a certain current density to verify the effect of the number of charge and discharge times on the specific capacity. In other words, the specific capacity of the three-phase composite sodium storage material is still more than 75% of the initial specific capacity after 1000 cycles at a current density in the range of 3.8A / g to 4.2A / g.
[0056] For example, under the condition of a current density of 4 A / g, the specific capacity of the three-phase composite sodium storage material decreases by 25%, 20%, 15% or 10% after 1000 cycles, which is not limited here.
[0057] Based on this scheme, the three-phase composite sodium storage material of the present application can maintain a high specific capacity after multiple cycles at a higher current density, indicating that the three-phase composite sodium storage material has good cycle stability and alleviates the disadvantage of the rapid decline in electrochemical performance of sodium ion batteries during charging and discharging.
[0058] In some embodiments, the initial electrochemical impedance of the three-phase composite sodium storage material is in the range of 0.015Ω~0.020Ω.
[0059] Exemplarily, the initial electrochemical impedance of the three-phase composite sodium storage material is 0.015Ω, 0.016Ω, 0.017Ω, 0.018Ω, 0.019Ω or 0.020Ω, etc., which is not limited here.
[0060] Based on this scheme, the initial electrochemical impedance of the three-phase composite sodium storage material of the present application is small. During the charge and discharge process of the sodium ion battery, the insertion and extraction of sodium ions will be easier, reducing the hindrance of the electrochemical reaction, helping to maintain the stability of the electrochemical performance of the sodium ion battery, and alleviating the disadvantage of the rapid decline in the electrochemical performance of the sodium ion battery during charge and discharge.
[0061] In a second aspect, the embodiments of the present application also provide a method for preparing a three-phase composite sodium storage material, such as Figure 1 As shown, the preparation method of the three-phase composite sodium storage material includes steps S1 to S3.
[0062] S1. Under alkaline conditions, react an iron source and a vanadium source to obtain a first precipitate.
[0063] Exemplarily, the alkaline condition may be a sodium hydroxide solution.
[0064] Exemplarily, the iron source provides iron element, and the iron source includes at least one of ferric chloride, ferrous chloride, ferric sulfate, ferric oxalate and ferric nitrate.
[0065] Exemplarily, the vanadium source provides vanadium element, and the vanadium source includes at least one of vanadium chloride, vanadium oxide and vanadium oxalate.
[0066] In some examples, the molar ratio of the iron source to the vanadium source ranges from 0.2 to 5.
[0067] For example, the molar ratio of the iron source to the vanadium source may be 0.2, 1.0, 1.8, 2.4, 3.2, 4.0 or 5, etc., which is not limited here.
[0068] The iron element in the iron source forms FeS with sulfur, and the vanadium element in the vanadium source forms V3S4 with sulfur. There are differences in the crystal structures of FeS and V3S4 themselves and in their electrochemical properties. When the molar ratio of the iron source to the vanadium source is small, for example, less than 0.2, or the molar ratio of the iron source to the vanadium source is large, for example, greater than 5, the imbalance caused by this difference will be aggravated, resulting in a decrease in the stability of the overall structure of the three-phase composite sodium storage material.
[0069] Based on this scheme, by adjusting the molar ratio of the iron source and the vanadium source within an appropriate range, the relative contents of FeS and V3S4 in the three-phase composite sodium storage material can be controlled. On the one hand, the overall stability of the structure of the three-phase composite sodium storage material can be improved; on the other hand, FeS and V3S4 can form a heterogeneous interface, and the adsorption energy required for sodium storage at the interface is low, which can make sodium ions more easily adsorbed at the interface, thereby improving the sodium storage capacity of the three-phase composite sodium storage material, improving the ion transport performance, and then improving the specific capacity of the three-phase composite sodium storage material, so as to improve the cycle stability and rate performance of the sodium ion battery electrode material.
[0070] In some embodiments, the first precipitate includes at least one of iron oxide, iron hydroxide, vanadium oxide, and vanadium hydroxide.
[0071] Iron oxide, iron hydroxide, vanadium oxide and vanadium hydroxide all have good compatibility with the sulfur source and carbon source components, which is beneficial to the subsequent hydrothermal reaction and the formation of a structurally stable three-phase composite sodium storage material.
[0072] S2. In an organic solvent, the carbon source, the first precipitate and the sulfur source are subjected to a hydrothermal reaction to obtain a second precipitate.
[0073] Exemplarily, the carbon source provides carbon elements and can be organic matter, for example, the carbon source includes at least one of polyvinyl pyrrolidone, glucose, polypyrrolidone and polydopamine. From the foregoing, it can be seen that the carbon material can form a close interface with FeS and V3S4, and can also promote the formation and stabilization of the heterogeneous interface.
[0074] Exemplarily, the sulfur source provides sulfur element, and the sulfur source includes at least one of thiourea, thioacetamide and sulfur powder. The sulfur source forms sulfide with iron element and vanadium element, so that FeS and V3S4 can be better compounded, which is conducive to forming a heterogeneous interface.
[0075] Exemplarily, the organic solvent is ethylene glycol.
[0076] In some embodiments, the molar ratio of the iron source to the sulfur source ranges from 2 to 5.
[0077] For example, the molar ratio of the iron source to the sulfur source may be 2, 3, 4 or 5, etc., which is not limited here.
[0078] In some embodiments, the mass of the carbon source is 10% to 20% of the total mass of the iron source, the sulfur source, and the vanadium source.
[0079] Illustratively, the mass of the carbon source is 10%, 12%, 14%, 16%, 18% or 20% of the total mass of the iron source, the sulfur source and the vanadium source, etc., which is not limited here.
[0080] Based on the above introduction to the iron source, carbon source and sulfur source, it can be seen that by adjusting the molar ratio of the iron source, carbon source and sulfur source, FeS and V3S4 are promoted to form a more stable heterogeneous interface, thereby improving the electrochemical performance of sodium ion batteries.
[0081] In some embodiments, the second precipitate includes at least one of an iron-sulfur compound and a vanadium-sulfur compound.
[0082] Iron-sulfur compounds and vanadium-sulfur compounds have stable crystal structures, can maintain structural integrity during the charge and discharge process, and can improve the cycle stability of sodium-ion batteries; moreover, iron-sulfur compounds and vanadium-sulfur compounds are combined with carbon sources to form a stable composite material structure, which is conducive to the formation of a structurally stable three-phase composite sodium storage material.
[0083] S3. Under inert gas conditions, calcining the second precipitate to obtain a three-phase composite sodium storage material.
[0084] During the calcination process, the organic matter in the second precipitate is pyrolyzed to generate carbon material, which is embedded in the structure of the sulfide. At the same time, calcination will also cause solid-phase reaction between the sulfides to form a more stable three-phase composite sodium storage material.
[0085] Wherein, the three-phase composite sodium storage material is selected from any one of the structures shown in the following general formula: (FeS) x / (V3S4) y / C; where 0.2≤x≤5, 0.2≤y≤5.
[0086] The three-phase composite sodium storage material obtained in the examples of the present application provides abundant sodium ion storage sites and more migration pathways for sodium ions.
[0087] In a third aspect, an embodiment of the present application also provides an application of the three-phase composite sodium storage material described in any of the above embodiments in a sodium ion battery electrode material.
[0088] The following is a further detailed description of the preparation method of the three-phase composite sodium storage material of the present application by using specific embodiments as examples and in conjunction with the accompanying drawings.
[0089] Example 1
[0090] The preparation method of the three-phase composite sodium storage material includes steps S11 to S13.
[0091] S11. Add 4 g of sodium hydroxide to 100 ml of deionized water, add 2 mmol of ferric chloride and 6 mmol of vanadium chloride after the sodium hydroxide is dissolved, stir for 30 minutes and then let stand for 2 hours, centrifuge to obtain a lower precipitate, and then dry to obtain a first precipitate.
[0092] Among them, ferric chloride is an iron source, and vanadium chloride is a vanadium source.
[0093] Exemplarily, the first precipitate is a white precipitate.
[0094] S12. Dissolve 1g of polyvinyl pyrrolidone in 50ml of ethylene glycol solvent, stir for 30 minutes, add 200mg of the first precipitate and 400mg of thiourea, stir for 30 minutes and add into the reactor, keep the reaction at 200℃ in a constant temperature box for 24 hours, then centrifuge and wash the reaction liquid after cooling, and obtain the second precipitate after vacuum drying.
[0095] Among them, polyvinyl pyrrolidone is the carbon source, ethylene glycol is the organic solvent, and thiourea is the sulfur source.
[0096] Exemplarily, the second precipitate is a black precipitate.
[0097] S13. Place 150 mg of the second precipitate in an argon-protected tubular furnace and treat it at 500° C. for 3 hours to obtain a FeS / V3S4 / C three-phase composite sodium storage material.
[0098] Figure 2 is the X-ray diffraction pattern of the three-phase composite sodium storage material of Example 1, from Figure 2 It can be concluded that all diffraction peaks can be indexed as FeS / V3S4, and no other impurity peaks appear, indicating that the FeS and V3S4 in the three-phase composite sodium storage material synthesized in Example 1 are of high purity.
[0099] Figure 3 and Figure 4 is a scanning electron microscope image of the three-phase composite sodium storage material of Example 1, wherein: Figure 3 and Figure 4 Taken from different positions of the three-phase composite sodium storage material, Figure 3 and Figure 4 It can be concluded that the morphology of the three-phase composite sodium storage material is cauliflower-like, with an average particle size of 4μm~10μm.
[0100] Figure 5 The transmission electron microscope image of the three-phase composite sodium storage material of Example 1 is shown in FIG. Figure 5The grain boundary L1 of FeS and V3S4 can be clearly seen, that is, there is an organic combination of two different substances. From the atomic point of view, the two substances interact with each other. In addition, from the morphology of the monomer and the morphology of the composite, FeS and V3S4 are not mixed. After the FeS / V3S4 composite is formed, the morphology changes greatly. This is because the difference in the lattice growth of the two during the synthesis process leads to the change in morphology.
[0101] Example 2
[0102] The preparation method of the three-phase composite sodium storage material of Example 2 is the same as that of Example 1, except that 2 mmol of ferric chloride is replaced by 1 mmol of ferric chloride, and 6 mmol of vanadium chloride is replaced by 9 mmol of vanadium chloride to obtain a (FeS)2 / (V3S4)6 / C three-phase composite sodium storage material.
[0103] Figure 6 is a scanning electron microscope image of the three-phase composite sodium storage material of Example 2, as shown Figure 6 As shown in the figure, the morphology of (FeS)2 / (V3S4)6 / C is cauliflower-like, and the average particle size is 4μm~10μm.
[0104] Example 3
[0105] The preparation method of the three-phase composite sodium storage material of Example 3 is the same as that of Example 1, except that 2 mmol of ferric chloride is replaced by 3 mmol of ferric chloride, and 6 mmol of vanadium chloride is replaced by 3 mmol of vanadium chloride to obtain a (FeS)3 / V3S4 / C three-phase composite sodium storage material.
[0106] Comparative Example 1
[0107] Comparative Example 1 provides a sodium storage material, and the preparation process of the sodium storage material includes steps: R1~R3.
[0108] R1. Add 4 g of sodium hydroxide into 100 ml of deionized water. After the sodium hydroxide is dissolved, add 4 mmol of ferric chloride. Stir slowly for 30 minutes and let stand for 2 hours. Centrifuge to obtain the lower precipitate, and then dry to obtain a white precursor powder.
[0109] R2. Dissolve 1g of polyvinyl pyrrolidone in 50ml of ethylene glycol solvent, stir vigorously for 30 minutes, then add 200mg of white precursor powder and 400mg of thiourea, stir for 30 minutes, add into the reactor, keep warm at 200℃ in a constant temperature box for 24 hours, then cool the reaction solution, centrifuge and wash, and vacuum dry to obtain black powder.
[0110] R3, 150 mg of black powder was placed in an argon-protected tubular furnace and treated at 500°C for 3 hours to obtain (FeS)4 / C sodium storage material.
[0111] Figure 7 is a scanning electron microscope image of the sodium storage material of Comparative Example 1, as shown Figure 7 As shown in , the morphology of the sodium storage material is spherical and the average particle size is 1μm~5μm.
[0112] Comparative Example 2
[0113] Comparative Example 2 provides another sodium storage material, and the preparation process of the sodium storage material includes steps: P1~P3.
[0114] P1. Add 4 g of sodium hydroxide to 100 ml of deionized water, add 12 mmol of vanadium chloride after it dissolves, stir slowly for 30 minutes and then let stand for 2 hours, centrifuge to obtain the lower precipitate, and then dry to obtain a white precursor powder.
[0115] P2. Dissolve 1g of polyvinyl pyrrolidone in 50ml of ethylene glycol solvent, stir vigorously for 30 minutes, then add 200mg of white precursor powder and 400mg of thiourea, stir for 30 minutes, add into the reactor, keep warm at 200℃ in a constant temperature box for 24 hours, then cool the reaction solution, centrifuge and wash, and vacuum dry to obtain black powder.
[0116] P3. Finally, 150 mg of black powder was placed in an argon-protected tubular furnace and treated at 500°C for 3 hours to obtain (V3S4)4 / C sodium storage material.
[0117] Figure 8 This is a scanning electron microscope image of the sodium storage material of Comparative Example 2, as shown Figure 8 As shown in the figure, the morphology of the sodium storage material is spherical and agglomerated together, with an average particle size of 1μm~5μm.
[0118] The following introduces the performance test data of sodium storage materials.
[0119] Test 1: The sodium storage materials obtained in Example 1, Comparative Example 1 and Comparative Example 2 were cycled for 150 to 200 cycles at a current density of 1 A / g to obtain the specific capacities of different sodium storage materials. The results are as follows: Fig. 9 shown.
[0120] from Fig. 9 It can be concluded that the sodium storage material (FeS)4 / C of comparative example 1 has a high specific capacity but a large attenuation, the sodium storage material (V3S4)4 / C of comparative example 2 has stable performance but a low specific capacity, and the three-phase composite sodium storage material of embodiment 1 has a high specific capacity and high stability. After 170 cycles, the specific capacity ranges from 500mAh / g to 600mAh / g.
[0121] Test 2: After the three-phase composite sodium storage material obtained in Example 1 was cycled for 1000 times at a current density of 4A / g, the charge specific capacity and discharge specific capacity of the three-phase composite sodium storage material were as follows: Fig.10 shown.
[0122] from Fig.10 It can be concluded that after 1000 cycles at a current density of 4A / g, the specific capacity of the three-phase composite sodium storage material decreased by 24%, and there was still 76% of the specific capacity remaining, indicating that the three-phase composite sodium storage material of the present application has good cycle stability performance.
[0123] Test 3: The sodium storage materials obtained in Example 1, Comparative Example 1 and Comparative Example 2 were heated to 0.05 Hz ~ 10 5 The initial electrochemical impedance test was carried out under the conditions of HZ test frequency and carbon content of 10%~15%. The results are as follows Fig.11 shown.
[0124] from Fig.11 It can be concluded that the initial electrochemical impedance of the three-phase composite sodium storage material obtained in Example 1 can be expressed as Fig.11 The diameter of the real part of the impedance of the semicircular figure in the figure, that is, the difference between the endpoint value of the real part of the impedance 0.028Ω and the initial value of the real part of the impedance 0.01Ω, obtains the initial electrochemical impedance of the three-phase composite sodium storage material is 0.018Ω, which is lower than the initial electrochemical impedance of the sodium storage material obtained in Comparative Example 1 and the initial electrochemical impedance of the sodium storage material obtained in Comparative Example 2, indicating that the three-phase composite sodium storage material of the present application improves the electrochemical performance of the sodium ion battery.
[0125] Test 4: The sodium storage materials obtained in Example 1, Comparative Example 1 and Comparative Example 2 were subjected to step rate performance tests. The specific capacities at current densities of 0.2 A / g, 0.5 A / g, 1 A / g and 2 A / g were as follows: Fig.12 shown.
[0126] from Fig.12 It can be concluded that at a current density of 0.2A / g, the specific capacity of the three-phase composite sodium storage material of Example 1 ranges from 600mAh / g to 700mAh / g; at a current density of 0.5A / g, the specific capacity of the three-phase composite sodium storage material of Example 1 ranges from 550mAh / g to 650mAh / g; at a current density of 1A / g, the specific capacity of the three-phase composite sodium storage material of Example 1 ranges from 550mAh / g to 600mAh / g; at a current density of 2A / g, the specific capacity of the three-phase composite sodium storage material of Example 1 ranges from 480mAh / g to 550mAh / g. Therefore, the three-phase composite sodium storage material obtained in Example 1 has a higher specific capacity, indicating that the three-phase composite sodium storage material of the present application has good rate performance.
[0127] The above are only specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a three-phase composite sodium storage material, characterized in that: include: Under alkaline conditions, reacting an iron source with a vanadium source to obtain a first precipitate; In an organic solvent, a carbon source, the first precipitate and a sulfur source are subjected to a hydrothermal reaction to obtain a second precipitate; Under inert gas conditions, the second precipitate is calcined to obtain a three-phase composite sodium storage material; wherein the three-phase composite sodium storage material is selected from any one of the structures shown in the following general formula: (FeS) x / (V3S4) y / C; where 0.2≤x≤5, 0.2≤y≤5.
2. The method for preparing the three-phase composite sodium storage material according to claim 1, characterized in that: The average particle size of the three-phase composite sodium storage material is in the range of 4 μm to 10 μm.
3. The method for preparing the three-phase composite sodium storage material according to claim 1 or 2, characterized in that: The three-phase composite sodium storage material has a specific capacity of 500 mAh / g to 600 mAh / g after 150 to 200 cycles at a current density of 0.8 A / g to 1.2 A / g.
4. The method for preparing the three-phase composite sodium storage material according to claim 1 or 2, characterized in that: The specific capacity of the three-phase composite sodium storage material decreases by less than or equal to 25% after 1000 cycles under the condition that the current density ranges from 3.8A / g to 4.2A / g.
5. The method for preparing the three-phase composite sodium storage material according to claim 1 or 2, characterized in that: The initial electrochemical impedance of the three-phase composite sodium storage material ranges from 0.015Ω to 0.020Ω.
6. The method for preparing the three-phase composite sodium storage material according to claim 1, characterized in that: The iron source includes at least one of ferric chloride, ferrous chloride, ferric sulfate, ferric oxalate and ferric nitrate.
7. The method for preparing the three-phase composite sodium storage material according to claim 1, characterized in that: The vanadium source includes at least one of vanadium chloride, vanadium oxide and vanadium oxalate.
8. The method for preparing the three-phase composite sodium storage material according to claim 1, characterized in that: The sulfur source comprises at least one of thiourea, thioacetamide and sulfur powder.
9. The method for preparing the three-phase composite sodium storage material according to claim 1, characterized in that: The carbon source comprises at least one of polyvinyl pyrrolidone, glucose, polypyrrolidone and polydopamine.
10. The method for preparing the three-phase composite sodium storage material according to claim 1, characterized in that: The molar ratio of the iron source to the vanadium source is in the range of 0.2 to 5.
11. The method for preparing the three-phase composite sodium storage material according to claim 1, characterized in that: The molar ratio of the iron source to the sulfur source is in the range of 2 to 5.
12. The method for preparing the three-phase composite sodium storage material according to claim 1, characterized in that: The mass of the carbon source is 10% to 20% of the total mass of the iron source, the sulfur source and the vanadium source.
13. The method for preparing the three-phase composite sodium storage material according to claim 1, characterized in that: The first precipitate includes at least one of iron oxide, iron hydroxide, vanadium oxide and vanadium hydroxide.
14. The method for preparing the three-phase composite sodium storage material according to claim 1, characterized in that: The second precipitate includes at least one of an iron-sulfur compound and a vanadium-sulfur compound.
Citation Information
Patent Citations
Electrode active material, electrode, and sodium secondary battery
CN102668192A
Heterojunction material, preparation method and application
CN117735618A